The Relationship Between Body Mass Index and Urinary Creatinine in Adolescent Girls - Nita Andriani Lubis; Geminsah Putra H Siregar; Mardan Ginting (Buletin Farmatera, 2020)
Adolscent girls phase (12-21 years) is a very important individual development segment, beginning with the maturation of physical and reproductive organs that characterize women of childbearing age. Body mass index (BMI) is one of indicator used to see women of childbearing age status related to pregnancy. Kidney damage causes an increase in urinary creatinine but high urinary creatinine does not necessarily indicate kidney damage. Our objective is to determine the relationship between BMI and urine creatinine  in adolscent girls in several Medan health schools. We performed an observasional study with cross sectional design of 56 participants   19-21 old girls. 24 hours urine creatinine concentration was measured using jaffe reaction method. The highest average BMI value (21.10 kg/m2 is the normal category (75%), mean urine creatinine concentration (1263,86 mg/24 hour) is also normal category. Data analysis with spearman correlation between BMI and 24-hour urine creatinine level was not statistically different (p = 0.140). High BMI values tend to have high 24-hour urine creatinine levels too, but statistically there was no significant relationship between 24-hour urine creatinine levels and BMI values in this study.